ACADEMIC RANK AND FACULTY UTILIZATION OF INTERNET INFORMATION IN RESEARCH PUBLICATIONS IN THE SOUTH SOUTH NIGERIA - Sunday, Oton Enobong (European Scientific Journal, ESJ, 2012)
The primary importance of Internet tools and services for the University faculty lies not in machines that will think for scholars but in scholars using such tools to amplify collective intelligence, bringing many minds together for more effective collaborative research and teaching. The adoption of the Internet has significantly influenced the research productivity of academics in many progressive ways and this paper outlines the prevailing situation among scholars in Universities in the South South region of Nigeria. The paper traces the evolution of the Internet, discusses its unique reach and capabilities and draws attention to the specific conclusion from the findings of the study that based on the research questions answered and hypotheses tested Academic Rank have no significant influence on lecturers’ utilization of Internet among academics in the South South zone of Nigeria.